Traumatic Pelvic Ring Injury following Childbirth with Complete Pubic Symphysis Diastasis - Aaron Seidman; Kelley Brossy; Alfred Faulkner; Jeffrey Taylor (Case Reports in Orthopedics, 2019)
Case. Traumatic pelvic ring injury following childbirth is a rare but debilitating condition. We present a case of a 28-year-old female who sustained a traumatic pelvic ring injury following childbirth with a complete pubic symphysis separation of 5.6 cm treated successfully with nonoperative management. Conclusion. Operative and nonoperative treatments for traumatic pelvic ring injuries following childbirth have been described without universal adoption of a uniform treatment modality. We hope this case study adds to the collection of data to help guide medical decision-making in the future as surgeons encounter patients with similar orthopedic injuries.